Factors Associated with BCG Scar of Pediatric Tuberculosis Patients at Pisangan and East Ciputat Community Health Centers - Farsida Farsida; Ayu Farah Syifa; Azka Zifa Tanama (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Tuberculosis (TB) is the most common cause of death in children.  Prevention of TB through Bacille Calmette–Guérin (BCG) vaccination is an action to produce immunity against TB disease.  After vaccination, a scar forms from the boil, which indicates a successful vaccination.  This study aims to determine the factors associated with BCG Scar in pediatric TB patients.  A cross-sectional design was conducted at the Pisangan and East Ciputat Community Health Centers in January-September 2020.  Data collection using medical records and telephone interviews on 35 samples was taken using the probability sampling technique, simple random sampling.  With inclusion criteria for pediatric TB patients (0-18 years) and exclusion criteria that do not include telephone numbers and addresses.  Bivariate analysis was used with the chi-square test.  The results showed a significant relationship between contact history and BCG scars in pediatric TB patients.  Age, gender, nutritional status, exclusive breastfeeding, immunization, mother's education, parent's occupation, family income, and smoking history were not significantly related to BCG scar.  Contact history related to BCG scar.  Parents should pay more attention to and protect their children from the people around them to cut off the possibility of contact with TB sufferers even though the child has been vaccinated.